Assessing Illumina technology for the high-throughput sequencing of bacteriophage genomes - Rihtman, Branko (PeerJ, 2016)
Bacteriophages are the most abundant biological entities on the planet, playing crucial roles in the shaping of bacterial populations. Phages have smaller genomes than their bacterial hosts, yet there are currently fewer fully sequenced phage than bacterial genomes. We assessed the suitability of Illumina technology for high-throughput sequencing and subsequent assembly of phage genomes. In silico datasets reveal that 30× coverage is sufficient to correctly assemble the complete genome of ~98.5% of known phages, with experimental data confirming that the majority of phage genomes can be assembled at 30× coverage. Furthermore, in silico data demonstrate it is possible to co-sequence multiple phages from different hosts, without introducing assembly errors.